MELINDUNGI KEANEKARAGAMAN HAYATI DALAM KERANGKA PROTOKOL NAGOYA - Mrs. Yulia; Zinatul Ashiqin Zainol (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2013)
The Nagoya Protocol is instrumental in the implementation of access and benefit sharing (ABS) in countries with biodiversity. There are however, weaknesses in the implementation of ABS, this includes the wide geographical spread of biodiversity and the difficulty in determining the benefitting owner of a certain area. Indonesia as a country blessed with biodiversity, has ratified the Nagoya Protocol through Act No. 11 of 2013, prepared amendment draft for the Patent Act and has further  prepared Draft Act on Genetic Resources. In the implementation of the Nagoya Protocal and ABS, Indonesia could refer to India’s experience in applying ABS and adapt such to accord itself with the Indonesian people’s background. Protokol Nagoya menjadi sarana dalam pelaksanaan access and benefit sharing (ABS) bagi negara-negara penyedia keanekaragaman hayati. Di dalam penerapan ABS terdapat kelemahan-kelemahan seperti tersebarnya keanekaragaman hayati dalam geografis yang luas dan sukarnya menentukan pemilik sebagai penerima keuntungan. Indonesia sebagai negara mega keanekaragaman hayati, telahmeratifikasi Protokol Nagoya melalui Undang-Undang Nomor 11 Tahun 2013, menyiapkan drafamandemen Undang-Undang Paten dan menyiapkan Rancangan Undang-Undang Sumber Daya Genetik. Dalam penerapan Protokol Nagoya dan ABS tersebut, Indonesia dapat mengacu dari pengalamanIndia dalam menerapkan ABS dengan menyesuaikan dengan latar belakang masyarakat Indonesia.